PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PENERAPAN BALANCED SCORECARD DAN KINERJA PERUSAHAAN - Syamsulbahri Syamsulbahri; Yusuf Gunawan; Hendra Noor Saleh; Jeffry Yuliyanto Waisapi (Journal of Innovation Research and Knowledge, 2026)
Increasing business competition requires organizations to adopt performance management systems that integrate both financial and non-financial aspects in a sustainable manner. The Balanced Scorecard (BSC) was developed as a strategic management tool to translate organizational vision and strategy into comprehensive performance indicators. However, in practice, the implementation of the Balanced Scorecard often faces challenges, particularly related to limited strategic understanding, organizational commitment, and leadership support. Transformational leadership is considered a relevant leadership style in driving organizational change, fostering employee engagement, and strengthening commitment to strategic objectives. This study aims to analyze the influence of transformational leadership on the implementation of the Balanced Scorecard and its implications for corporate performance. The study employed a qualitative research approach using a case study design. Data were collected through in-depth interviews, observations, and document analysis involving top management, managers, supervisors, and key employees directly engaged in the Balanced Scorecard implementation. Data were analyzed using thematic analysis techniques. The findings indicate that transformational leadership plays a crucial role in shaping strategic understanding, enhancing organizational commitment, and ensuring the effective integration of Balanced Scorecard perspectives. The implementation of the Balanced Scorecard supported by transformational leadership contributes positively to corporate performance improvement, encompassing both financial and non-financial dimensions.